Welfare, inequality and financial effects of a multi-pillar pension reform: the case of Peru - Olivera, Javier (2016)
This paper studies the potential effects of a multi-pillar pension system on pension inequality, actuarial liability and welfare in Peru, by means of simulations of future distributions of pensions with social security administrative records. The results show that actual pension inequality and actuarial liability can be substantially reduced with welfare preserving policies. The simulations illustrate that when welfare is considered, it is important to define the implied value judgments, which are not universally agreed upon. Therefore, this paper highlights the trade-offs of a pension policy reform and contributes to assess the second generation of pension reforms in Latin America. - Reproduced.
Keywords: Social welfare - Peru; Pensions - Peru; Pensions